PENDEKATAN “RELIGIOUS MARKETING” DALAM KOMUNIKASI ISLAM MENJAWAB TANTANGAN ERA DISRUPSI - Muhammad Mabrur (UIN Antasari Banjarmasin, 2020)
The rapid development of information technology has influenced the behavior of modern human life. Findings after findings have made modern humans connected with each other. Impact The emergence of new business features that shift the old life patterns. This is where disruption begins. Disruption is a change in various sectors of life as a result of digitalization and the